Design code review on seismic demand and base detailing criteria: an application to wine tanks in Marlborough - Frezzati, Marco; Loporcaro, Giuseppe; Buratti, Nicola; Palermo, Alessandro; Walker, Adam (Frontiers in Built Environment, 2023)
Marlborough is the largest wine-growing region of New Zealand. The seismic events of Lake Grassmere 2013 and Kaikōura 2016 caused severe business disruption to the wineries due to the poor performance of wine storage tanks and connected non-structural components. The damage recorded raised two main discussions concerning the NZSEE 2009 guideline - Seismic design of liquid storage tanks. The first is related to the appropriateness of the determination of the importance level to adopt for the design of tanks. In fact, an importance level 1 (“Structures presenting a low degree of hazard to life and other property”) was adopted for most wine tanks and therefore the horizontal forces they were designed for were extremely low. Adopting an importance level 2 (“Normal structures”) would have increased the overall seismic demand to design them for and therefore limit their structural damage but potentially increase the structural cost. The second concerns the design detailing of the critical connections. In fact, the current guidelines/standards lack provisions. The authors compare the NZSEE 2009 guideline with Eurocode 8 (EC8) and API650 through the design of six tanks with typical dimensions used in the New Zealand wine industry. Results show that assigning importance level 1 results in seismic design demand similar to EC8 and API650 and therefore showing that other countries have a similar approach to New Zealand. A further comparative analysis also highlighted that connection detailing design including hierarchy of strength is totally missing in all three standards/guidelines lack information.